2003
DOI: 10.1023/b:caco.0000003837.10664.7f
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anal cancer: results of a population-based case–control study

Abstract: The results of this study suggest that both sexual and non-sexual factors are important in the etiology of anal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
7
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(197 citation statements)
references
References 21 publications
11
172
7
7
Order By: Relevance
“…In this study, we observed an increased risk for invasive (OR 5 2.3), but not in situ, penile cancer (OR 5 1.1) among men not circumcised in childhood, consistent with the findings of Tseng et al 5 Here and in other studies, 2,5,12,13 a history of phimosis was a strong risk factor for penile cancer. Interestingly, though it was a risk factor for both invasive and in situ disease, the proportions of subjects with invasive and in situ penile cancer who reported a history of phimosis (47% and 21%, respectively) were different (v 2 p for difference 5 0.02).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we observed an increased risk for invasive (OR 5 2.3), but not in situ, penile cancer (OR 5 1.1) among men not circumcised in childhood, consistent with the findings of Tseng et al 5 Here and in other studies, 2,5,12,13 a history of phimosis was a strong risk factor for penile cancer. Interestingly, though it was a risk factor for both invasive and in situ disease, the proportions of subjects with invasive and in situ penile cancer who reported a history of phimosis (47% and 21%, respectively) were different (v 2 p for difference 5 0.02).…”
Section: Discussionsupporting
confidence: 91%
“…Potential risk factors are compared to biologic markers of HPV exposure through testing of pathologic specimens for HPV DNA in cases and testing for serum HPV16 antibodies in both cases and controls. Because circumcision status has been shown to modify the risk of penile cancer in previous studies, 2,5 circumcision status and the timing of the procedure are given special attention.…”
mentioning
confidence: 99%
“…119,120 These studies show an association between circumcision and a decreased likelihood of invasive penile cancer. For all men with penile cancer (carcinoma in situ and squamous cell carcinoma), the absence of circumcision confers an increased risk with an odds ratio (OR) of 1.5, although this finding was not significant (P = .07), with a CI of 1.1-2.2.…”
Section: Cancer Penile Cancermentioning
confidence: 94%
“…Systematic reviews show that circumcised men are at significantly lower risk of syphilis and chancroid. 8,9 Circumcised men in the United States are also at significantly lower risk of invasive penile cancer, [10][11][12][13] and a lower risk of cervical cancer in partners of circumcised men has also been reported. 14 This may be due to decreased human papillomavirus infection, which causes ano-genital and cervical cancer.…”
Section: Non-hiv-related Benefits To Women Of Male Circumcisionmentioning
confidence: 99%